Identifikasi Risiko Keselamatan Pekerja Dengan Metode FMEA di Departemen Produksi PT. XYZ - Muhammad Rifqi Saifudin; Sukanta Sukanta (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2023)
This research was carried out because it is known that there are six potential work accidents that can occur production departments of PT. XYZ. PT XYZ, so it is necessary to identify employee safety risks to obtain the right solution to prevent the occurrence of work accidents, and the method chosen is failure mode and effect analysis. FMEA is a table-shaped identification tool that is useful for identifying errors, evaluating the effects of errors, and prioritizing errors. Data collection is carried out through observations, interviews, and discussions with employees in production departments of PT. XYZ. Accidents that are the main priority to resolve first are milling machine operators injured due to exposure to grams of iron that can result in delayed operator work because the accident has the largest RPN value of 210, with details of severity 6, occurrence 7, and detection 5. The conclusion of this study is that PT. XYZ, which does not provide self-protection equipment for workers in the production department, is the most prevalent cause of work accidents, so more attention should be paid to the procurement of protective equipment and requiring workers to wear it.